Study and Comparative Analysis of Programming Languages Used for Big Data - Mahmudova, Shafagat (Review of Information Engineering and Applications, 2021)
This article provides information about the industrial revolutions and analyzes the Fourth Industrial Revolution. The Fourth Industrial Revolution takes away the potential risks of unsustainable growth and world systems, and its coming is estimated as a challenge. The main technologies of the Fourth Industrial Revolution are identified. Big data technologies enable to handle different types of data at the same time. Big data is very important among technologies. The difference between big data and usual data is that the volume of Big Data starts at terabytes. The types technologies used for big data are explained. The programming languages used for big data are extensively analyzed. Their similarities and differences are compared. Big data will be among the most required information technologies. The article analyzes the literature in this area and data analysis methods for Big data. There are other criteria that emphasize the need for new methods to work with big data.